2012
DOI: 10.1371/journal.pone.0036478
|View full text |Cite
|
Sign up to set email alerts
|

High Nutrient Transport and Cycling Potential Revealed in the Microbial Metagenome of Australian Sea Lion (Neophoca cinerea) Faeces

Abstract: Metagenomic analysis was used to examine the taxonomic diversity and metabolic potential of an Australian sea lion (Neophoca cinerea) gut microbiome. Bacteria comprised 98% of classifiable sequences and of these matches to Firmicutes (80%) were dominant, with Proteobacteria and Actinobacteria representing 8% and 2% of matches respectively. The relative proportion of Firmicutes (80%) to Bacteriodetes (2%) is similar to that in previous studies of obese humans and obese mice, suggesting the gut microbiome may co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…Our findings greatly expand upon observations describing the fecal microbiota of a single sea lion determined from feces collected from Seal Bay, Kangaroo Island, Australia, in which Firmicutes contributed ϳ80% to the microbial community composition (5,18,20). Similar fecal microbiota composition and Firmicutes dominance have been observed in other pinniped species, including Australian fur, leopard, southern elephant, and Weddell seals, suggesting that the Firmicutes are a core group within the pinniped microbiota.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings greatly expand upon observations describing the fecal microbiota of a single sea lion determined from feces collected from Seal Bay, Kangaroo Island, Australia, in which Firmicutes contributed ϳ80% to the microbial community composition (5,18,20). Similar fecal microbiota composition and Firmicutes dominance have been observed in other pinniped species, including Australian fur, leopard, southern elephant, and Weddell seals, suggesting that the Firmicutes are a core group within the pinniped microbiota.…”
Section: Discussionsupporting
confidence: 79%
“…However, marine mammal samples used for studies and comparisons of microbiota have almost entirely come from seals of various species (5,(17)(18)(19)(20)(21). Such studies have found that the microbiota are largely dominated by four phyla, Firmic-utes, Bacteroidetes, Fusobacteria, and Proteobacteria, and, to a lesser extent, by Actinobacteria (5,(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…In order to increase existing data on the marine mammal microbiome, logistically feasible, nonor minimally-invasive sampling protocols that are easily reproducible and provide biological material suitable for a range of studies are necessary. For example, respiratory blow can be used to examine host DNA 42 and hormone levels 43,44 as well as respiratory associated microorganisms 19,33,37 , while non-invasively collected fecal samples can be used to study host DNA 45 , prey items 46 and the gut microbiome 22,23 .…”
Section: Sampling Techniquesmentioning
confidence: 99%
“…Designing studies that control for host variation will allow us to make headway in our understanding of disease manifestation. Studies that focus on the functionality of the microbiome will reveal the interactions between host and the microbial community 23,56 . In human subjects, similar target investigations have allowed for the development of novel metabolites to treat and prevent disease 57 .…”
Section: Sampling Techniquesmentioning
confidence: 99%
“…Several studies focused on microbial functions for specific animals (c.f. Lavery et al, 2012;Tun et al, 2012), and a global metagenomic screen across Mammalia demonstrated that the bacterial functional repertoire is primarily governed by diet and does not reflect host phylogeny (Muegge et al, 2011). That study revealed that the microbiota in carnivores and herbivores are characterized by different trade-offs in amino-acid pathways and by an opposite directionality in the central phosphoenolpyruvate-pyruvate-oxaloacetate cycle.…”
Section: Introductionmentioning
confidence: 97%